Development of a PIGE-Detection System for in-situ Inspection and Quality Assurance in the Evolution of Fast Rotating Parts in High Temperature Environment Manufactured from TiAl - S. Neve; H.-E. Zschau; P.J. Masset; M. Schütze (Atom Indonesia, 2013)
Intermetallic γ-titanium aluminides are a promising material in high temperature technologies. Their high specific strength at temperatures above 700°C offers the possibility for their use as components of aerospace and automotive industries. With a specific weight of 50% of that of the widely used Ni-based superalloys TiAl is very suitable as material for fast rotating parts like turbine blades in aircraft engines and land based power stations or turbocharger rotors. Thus lower mechanical stresses and a reduced fuel consumption and CO2-emission are expected. To overcome the insufficient oxidation protection the halogen effect offers an innovative way. After surface doping using F-implantation or liquid phase-treatment with an F-containing solution and subsequent oxidation at high temperatures the formation of a protective alumina scale can be achieved. By using non-destructive ion beam analyses (PIGE, RBS) F was found at the metal/oxide interface. For analysis of large scale components a new vacuum chamber at the IKF was installed and became operative. With this prototype of in-situ quality assurance system for the F-doping of manufactured parts from TiAl some performance test measurements were done and presented in this paper.Received: 01 March 2013; Revised: 24 April 2013; Accepted: 25 April 2013